Identification of fragmented cropland in arid and semiarid sandy areas: a case study of horqin left rear banner - Sang, Zhiting; Liang, Jie; Zheng, Huihui; Wang, Kaige; Xu, Yan; Liu, Yibin (Frontiers in Environmental Science, 2022)
The sustainable development and utilization of sandy areas in arid and semiarid regions is of strategic importance to ensure both food and ecological security. The unique geographical environment of these areas and uncontrolled exploitation by farmers lead to large amounts of fragmented cropland. Despite government management, the quantity and distribution of these fragmented croplands is unknown, and accurate identification of the region's fragmented croplands can provide data to support the sustainable use of sandy areas. We propose a method for identifying fragmented cropland based on scale transformation. Small-scale fragmented cropland is approximately represented at larger scales, so we apply small-scale high-resolution remote sensing images to identify features and obtain information at a large scale, i.e., the ratio of fragmented cropland area. By correcting the cropland areas identified from low-resolution remote sensing images and using them as the basis for the resulting calculation, more accurate identification can be achieved at a large scale. In this study, this method was applied based on remote sensing images with 0.54 m and 30 m resolutions that were acquired during the same period, using Horqin Zuoyihou Banner as the study area. The results showed that (1) there was 13637.08 hm2 of fragmented cropland in Horqin Zuoyihou Banner due to precipitation and terrain topography, mainly in the central and western regions and (2) identification at the sample point scale and plot scale were positively correlated in area and showed a consistent distribution. Therefore, accurate and efficient identification of fragmented cropland can be achieved through scale transformation.